PELAKSANAAN PEMBAGIAN HARTA WARISAN TERHADAP AHLI WARIS PENGGANTI MENURUT HUKUM ISLAM DAN HUKUM PERDATA: Hilman Ajie Indra - admin, admin (Reformasi Hukum, 2018)
The result of his research is that the position of heir substitute according to Islamic law has been explained in Article 185 paragraph (2) Compilation of Islamic Law which states "The part of the substitute heir may not exceed the heirs of equal heirs. The position of substitute heirs according to civil law is stated in Article 832 of the Civil Code which states that "According to the law, the right to be an heir is a blood family, both lawful and out of wedlock, and husband or the wife who lives the longest, according to the following rules. If the blood relatives and the husband or wife who live the longest are not present, then all inheritance becomes the property of the state, which is obliged to pay off the debts of the deceased person, insofar as the inheritance price is sufficient for that ”; (b). The formulation of Article 185 paragraph (1) that uses the phrase "can be replaced" raises the uncertainty of the appearance of substitute heirs. The word "can" contains an understanding that is facultative or tentative so that it can be interpreted as an heir that may be replaced and some may not be replaced. In Article 841 of the Civil Code, it is stated that "Replacement gives the right to someone who changes, to act as a substitute, in the degree and in all rights of the person who is replaced"; and (c). In Islamic Law, the distribution of inheritance to substitute heirs has been explained in Article 174 paragraph (1) letter a stating that the substitute heirs will get a portion of the portion of the heirs who are replaced. Al-Qur'an has also been clearly explained and stated in Surah An-Nisa verse 33 which states that "For each inheritance from the assets left by the mother of father and close relatives, we make the heirs-heirs. And (if any) people who have sworn their loyalty to them, then give them their share. Verily Allah witnesses everything. As stipulated in Articles 842, 844 and 845 of the Civil Code, from the first event (Article 842 and 844 of the Civil Code) there are in the Civil Code, and the third event (Article 845 of the Law Civil Code) is an addition.